2019
DOI: 10.1039/c8na00416a
|View full text |Cite
|
Sign up to set email alerts
|

Will organic–inorganic hybrid halide lead perovskites be eliminated from optoelectronic applications?

Abstract: In the development of perovskite solar cells, a new version of Don Quixote is needed if scientists are to keep on seeking the most celebrated works of literature, according to the evaluation criterion of ‘THE FIRST’ and ‘THE BEST’.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
109
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(112 citation statements)
references
References 97 publications
0
109
0
3
Order By: Relevance
“…The size of cation A must be larger than that of cation B. Ideally, perovskite crystal structure is described as a body centered cubic structure with monovalent cation A dodecahedrally (12‐fold) coordinated by X anions as shown in Figure . The volume occupied by A ions depends on the electronegativity and size of B and X ions, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The size of cation A must be larger than that of cation B. Ideally, perovskite crystal structure is described as a body centered cubic structure with monovalent cation A dodecahedrally (12‐fold) coordinated by X anions as shown in Figure . The volume occupied by A ions depends on the electronegativity and size of B and X ions, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The octahedral factor (μ) must lie in the range of 0.44–0.72 for B and X in order to form a stable BX 6 octahedron . The tolerance factor has an immense role to play in finding alternative lead halide perovskite materials as many different cations can be inserted in ABX 3 structure framework leading to development of varied materials with specific engineered properties …”
Section: Introductionmentioning
confidence: 99%
“…Notably, Sn‐based PSC devices have recently shown promising PCE approaching 10% . Nevertheless, the easy oxidization of Sn 2+ to Sn 4+ and Ge 2+ to Ge 4+ leads to the instability of PSC devices in ambient condition, which remains the biggest challenge in Sn‐ or Ge‐based PSCs . In addition to Sn or Ge, another candidate for the substitution of Pb 2+ is non‐toxic Bi 3+ and Sb 3+ in the V main group, but their corresponding 0D or 2D A 3 B 2 X 9 crystal structure tends to strongly bound excitons, leading to low charge mobility and inferior photovoltaic performance …”
Section: Introductionmentioning
confidence: 99%
“…The Ni 2+ ‐passivated device maintained 90% of its initial PCE in an environment of AM 1.5G 1 sun and air equivalent irradiance (temperature ≈25 ° C, humidity ≈45 RH%) for 150 h. In addition, the experiment also found that MAPbI 3 (Ni 2+ ) has a maximum steady‐state output power at 0.95 V and a higher stability at the maximum steady‐state output power. Therefore, doping and passivation engineering hold great promising to improve the stability of MAPbI 3 to meet the criteria mentioned above …”
Section: Methods For Improving the Stability Of Oihp‐based Solar Cellsmentioning
confidence: 99%